Effector diversification within compartments of the Leptosphaeria maculans genome affected by Repeat-Induced Point mutations - Rouxel, Thierry; Graubert, Jonathan; Hane, James K.; Hoede, Claire; Van de Wouw, Angela P.; Couloux, Arnaud; Dominguez, Victoria; Anthouard, Véronique; Bally, Pascal; Bourras, Salim; Cozijnsen, Anton J.; Ciuffetti, Lynda M.; et al. (Macmillan Publishers Limited, 2011)
Fungi are of primary ecological, biotechnological and economic importance. Many fundamental biological processes that are shared by animals and fungi are studied in fungi due to their experimental tractability. Many fungi are pathogens or mutualists and are model systems to analyse effector genes and their mechanisms of diversification. In this study, we report the genome sequence of the phytopathogenic ascomycete Leptosphaeria maculans and characterize its repertoire of protein effectors. The L. maculans genome has an unusual bipartite structure with alternating distinct guanine and cytosine-equilibrated and adenine and thymine (AT)-rich blocks of homogenous nucleotide composition. The AT-rich blocks comprise one-third of the genome and contain effector genes and families of transposable elements, both of which are affected by repeat-induced point mutation, a fungal-specific genome defence mechanism. This genomic environment for effectors promotes rapid sequence diversification and underpins the evolutionary potential of the fungus to adapt rapidly to novel host-derived constraints.